(untitled) - Sartirano, G.R.=700 1 Ribot, J.J.; Puglisi, G.
(En, Es)
Ilus., 7 ref.
Keywords: EXPORTACIONES; CARNE; NORMAS; SANIDAD ANIMAL; INOCUIDAD ALIMENTARIA; MADAGASCAR; REVISTA MUNDIAL DE ZOOTECNIA